3D digital holographic polarimetry of laser speckle fields formed by polycrystalline blood films: a tool for differential diagnosis of thyroid pathology - Olexander Ushenko; Olexander Ushenko; Olexander Bilookyi; Jun Zheng; Alexander Dubolazov; Olexander Olar; Olexander Olar; Yurii Ushenko; Yurii Ushenko; Iryna Soltys; Ivan Mikirin; Valeriy Skliarchuk; et al. (Frontiers in Physics)
The principles and effectiveness of the method of laser polarization interferometry of dehydrated blood films (facies) for the differential diagnosis of thyroid pathology have been studied. For this purpose, a theoretical description of the processes of formation and layer-by-layer phase scanning of the polarization structure of speckle fields in the blood facies of donors and patients with nodular goiter, autoimmune thyroiditis, and papillary cancer has been developed for the first time. A statistical analysis of holographically reconstructed maps of polarization ellipticity of the singly scattered component of the speckle field was conducted. Based on this analysis, the most sensitive markers for the diagnosis and differentiation of thyroid pathology were identified. Excellent diagnostic accuracy (91%–93%) and very good differentiation accuracy (86%–89%) were achieved for nodular goiter, autoimmune thyroiditis, and papillary cancer.